Evaluasi Dan Perancangan Sistem Pengendalian Internal Atas Persediaan Menggunakan COSO (Studi Kasus Pada Cihanjuang Inti Teknik) - Dea Setiana; Sugih Sutrisno Putra (Indonesian Accounting Literacy Journal, 2021)
SPI is one of the contro1s in managing inventory. Effective and efficient management of SPI on inventory will reduce the potentia1 for fraud and 1oss in the company. Based on pre1iminary studies, SPI at Cintek is still not effective and efficient due to monitoring and not imp1ementing SOPs by the division re1ated to supp1ies. The purpose of this study is to assess how effective and efficient the existing SPI is and then provide recommendations in the form of a design to improve the SPI in the company. This research was conducted using qualitative descriptive method case study approach and data co11ection techniques in the form of interviews, observation and documentation. The SPI design that the writer made was in the form of SOP using a contro1 matrix. The research results will be obtained in the form of recommendations to companies in increasing the effectiveness and efficiency of SPI on supplies.